Kōrero Mai - Te Hurinui Karaka-Clarke; Jo Fletcher; Angus Macfarlane; Bryanna Bell (Flexible Learning Association of New Zealand, 2022)
Online teaching and learning programmes allow ākonga who live in isolated areas, or who have differing learning requirements, to study by distance. Maintaining student engagement in the online environment is an important aspect. This article explores how kaiako (teachers) can engage their ākonga (students) better in online environments. The article has a particular emphasis on supporting Māori learners, who represent 25% of the New Zealand school population. Five kaiako were interviewed about their experience of teaching New Zealand secondary school students online. The study found that the kaiako had some awareness of bicultural values and practices, but lacked confidence in embedding it in their online teaching, which was limited to synchronous timetabled sessions with some communication by text and email. The time provided for online students was considerably less than for the secondary students in traditional classrooms.